Acceptance of seasonal influenza vaccination and associated factors among pregnant women in the context of COVID-19 pandemic in China: a multi-center cross-sectional study based on health belief model - Ruitong Wang; Liyuan Tao; Na Han; Jihong Liu; Chuanxiang Yuan; Lixia Deng; Chunhua Han; Fenglan Sun; Liqun Chi; Min Liu; Jue Liu (BMC, 2021)
Abstract Background Seasonal influenza can circulate in parallel with coronavirus disease (COVID-19) in winter. In the context of COVID-19 pandemic, the risk of co-infection and the burden it poses on healthcare system calls for timely influenza vaccination among pregnant women, who are the priority population recommended for vaccination. We aimed to evaluate the acceptance of influenza vaccination and associated factors among pregnant women during COVID-19 pandemic, provide evidence to improve influenza vaccination among pregnant women, help reduce the risk of infection and alleviate the burden of healthcare system for co-infected patients. Methods We conducted a multi-center cross-sectional study among pregnant women in China. Sociodemographic characteristics, health status, knowledge on influenza, attitude towards vaccination, and health beliefs were collected. Locally weighted scatterplot smoothing regression analysis was used to evaluate the trends in the acceptance of influenza vaccine. Logistic regression was applied to identify factors associated with vaccination acceptance. Results The total acceptance rate was 76.5% (95%CI: 74.8-78.1%) among 2568 pregnant women enrolled. Only 8.3% of the participants had a history of seasonal influenza vaccination. In the logistic regression model, factors associated with the acceptance of influenza vaccine were western region, history of influenza vaccination, high knowledge of influenza infection and vaccination, high level of perceived susceptibility, perceived benefit, cues to action and low level of perceived barriers. Among 23.5% of the participants who had vaccine hesitancy, 48.0% of them were worried about side effect, 35.6% of them lacked confidence of vaccine safety. Conclusions Our findings highlighted that tailored strategies and publicity for influenza vaccination in the context of COVID-19 pandemic are warranted to reduce pregnant women's concerns, improve their knowledge, expand vaccine uptake and alleviate pressure for healthcare system.